The role of Thompson score of term newborns in predicting neuromotor outcome at 1 year of age - Subham Puhan; Saugata Chaudhuri (Asian Journal of Medical Sciences, 2024)
Background: The mortality rate is approximately 20% and the frequency of neurodevelopmental sequelae in surviving newborns is approximately 30% in perinatal asphyxia; hypoxic-ischemic encephalopathy (HIE) is brain dysfunction due to lack of oxygen and blood supply to the brain. Aims and Objectives: This study was conducted to predict the pattern of neuromotor outcome as early as 3 months using Hammersmith Infant Neurological Examination (HINE) in term hypoxic babies and its relation with the Thompson score (HIE score). Materials and Methods: One-hundred twenty four term newborns with hypoxic babies were admitted to the neonatal care unit from January 2021 to August 2021. Thompson scoring was done on admission and subsequently reviewed. Discharged babies were followed up at 3 months, 6 months, and 1 year of age. A neurological examination (HINE) was done in this high-risk follow-up clinic. Maximum Thompson score was correlated with neurological score at various months. The earliest predictability of neurological examination was done at 3 months and was correlated with the neurological examination done at 12 months. Results: The correlation between the Thompson score and the 3-month score is −0.65 indicating a strong negative association between the two measurements. The correlation between 3 months and 6 months and 1-year neurological scores was moderately associated with each other. Conclusion: The maximum Thompson score was significantly higher in the mortality group compared to the discharged group. Thompson score has a significant correlation with the 3, 6, and 12-month neurological scores examined by HINE. The 3-month neurological outcome has a very significant correlation with the 1-year outcome.